Institute of Metals Division - The Effect of Neutron Irradiation on Slip Lines in Molybdenum - J. L. Brimhall (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1965)
Slip-line formation during bending has been studied on neutron-irradiated molybdenum single crystals. For equivalent strains, the slip lines are coarse and distinct in the irradiated molybdenum and not resolvable in the unirradiated molybdenum. The slip lines have been directly correlated with dislocation channels present in the irradiated and deformed thin foils. The heterogeneous distribution of the dislocations during deformation in the irradiated material results from dislocation interaction with the dejects produced during irradiation. Impurities , in the form of' carbides, affected the dislocation channeling Principally by acting as dislocation sources. ALTHOUGH the mechanical behavior of irradiated materials has been studied extensively, the precise mechanism of irradiation hardening has not been established. Some information on the microstructural species responsible for hardening of irradiated materials has been derived from direct and indirect observations. The direct observation of the structure of deformed irradiated metals, particularly by transmission electron microscopy, is a relatively new and unexplored area. Slip-line studies in fcc metals have been restricted primarily to copper.1-3 Very coarse slip lines, representing slip on many closely spaced planes, have been observed in deformed, irradiated copper. Coarse slip lines have also been observed in irradiated aluminum.4 Clear channels in irradiated copper caused by dislocation motion through the defect structure have been seen by transmission electron microscopy and correlated with slip lines.5-6 To date, little work has been reported on the irradiated bcc metals. Eyre described the slip lines around hardness indentations on irradiated iron and found them to be more distinct than lines in unirradiated material.' Mastel et al.' have observed channels in deformed irradiated molybdenum similar to those reported in copper. As part of a program concerned with the effect of neutron irradiation on metals, the slip-line